Sukuh and Cetho Temples: A Comparative Study of History, Architect, and Culture - Isawati; Musa Pelu; Nur Fatah Abidin (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2023)
Sukuh Temple and Cetho Temple are relics of high value and inherit the values of life for the surrounding community. Archaeologically these two temples have differences. On that basis, the problem in this study is how to compare the history of Sukuh Temple and Cetho Temple as well as from architectural and cultural aspects. This article then aims to explain the similarities and differences in the historical, architectural and cultural aspects of Sukuh and Cetho Temples. The research method used is qualitative with an exploratory study that is descriptive naturalistic in nature. The results showed that the Sukuh and Cetho Temples were built during the Majapahit Kingdom. In the architectural aspect, Sukuh and Cetho Temples have similarities and differences related to the shape, location and arrangement of the reliefs. In terms of cultural aspects, the people around Sukuh and Cetho Temples have local traditions and culture, namely Grebek Sukuh, Ruwatan Tradition, Galungan Ceremony, Dawuhan, Pancawali Krama and Medang Siang. This tradition contains religious values, mutual cooperation, togetherness and tolerance values.